Studies on correlation between electronic structure and electronic conductivity in MoX2 (X = S, Se and Te) - Muhamad Haikal Hazazi, Mohd Rusland (2016)
A successful research have been conducted to investigate the molybdenum dichalcogenides, MoX2 (X = S, Se, and Te) as the electrode materials in electrochemical cells. The relationship between number of layer and bandgap of the materials has been studied by many researcher in the past. They hardly stated that, the properties such as speed of storage and amount of chargers that could be stored within the cells will be answered as soon as the correlation been studied. In this study, fundamental parameters such as size-offset between a monolayer and exciton Bohr radius of MoX2 and ground and excited state electron density have been investigate. In this study also, realistic monolayer models of MoX2 were identified using quantum chemical calculations which also explain a correlation between size-offset and charge storage properties. We conclude that as the size-offset decreases, the higher possibility of wave functions overlap between the excited state, and ground state electrons; therefore the higher the electron mobility, and conductivity of the MoX2 would be.